Implications of the PNG-US Defense Pact for Indonesia's Sovereignty and National Interests - Wiyono, Wujud; Supriyanto, Taufiq (PT FORMOSA CENDEKIA GLOBAL, 2024)
On May 22, 2023, Papua New Guinea signed a defense pact with the United States. This pact gives US troops access to airfields and ports in Papua New Guinea, which is part of US efforts to reduce China's influence in the Pacific region. The presence of US troops in Papua New Guinea could affect the stability of the surrounding region. Indonesia must ensure that its territory remains safe and is not threatened by foreign military presence in neighboring countries. Good communication is needed between Indonesia, Papua New Guinea and the US to ensure that military actions do not violate Indonesia's territorial sovereignty. The implications for Indonesia's national security must be considered. The presence of US troops near the Indonesian border could affect security dynamics in the region. Indonesia must ensure that foreign military presence does not threaten its national stability and security. Papua New Guinea and Indonesia have important regional ties. Cooperation in the defense sector must strengthen stability and security in the Pacific region. Indonesia needs to ensure that cooperation with Papua New Guinea and the US does not damage bilateral relations with neighboring countries. This research aims to understand how defense cooperation between Papua New Guinea and the United States can influence Indonesia's national interests, as well as to provide policy recommendations related to maintaining Indonesia's sovereignty and national interests in the context of the agreement. The research method used in this research is a qualitative research approach with a case study method.